Comparison of Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio as a Predictor of Clinical Outcome in Acute Ischemic Stroke - Anthony Gunawan; Ashari Bahar; Irbab Hawari; Wijoyo Halim (Journal of Neurointervention and Stroke, 2025)
Highlight: NLR and PLR are associated with stroke outcomes They may influence outcomes via thromboinflammatory pathways ABSTRACT Introduction: Stroke is a clinical syndrome characterized by neurological deficits lasting more than 24 hours or resulting in death, caused exclusively by cerebrovascular disease. Stroke is a leading cause of mortality, responsible for 7.8 million deaths worldwide each year and accounting for 13% of all deaths. Several studies have revealed the role of neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in predicting stroke. However, no study has directly compared NLR and PLR levels with the clinical outcomes of acute ischemic stroke (AIS). Objective: This study aims to compare the predictive value of the NLR and PLR with the clinical outcome of AIS based on the Modified Rankin Scale (mRS) and with the incidence of early neurological deterioration (END) based on NIHSS. Method: This was a prospective observational study. NLR and PLR values were obtained from routine blood examinations, and stroke outcome were assessed using the mRS. Result: A total of 125 ischemic stroke patients met the inclusion criteria. Chi-square test showed that NLR was associated with mRS outcomes, with an odds ratio (OR) of 6.1, while PLR was associated with mRS with an OR of 5.6. Fisher's exact test revealed a statistically significant association between NLR and the incidence of END (OR 19.26; p<0.001), as well as between PLR and END (OR 5.9; p=0.003). Conclusion: NLR and PLR have predictive value for both clinical outcome and the incidence of END in patients with acute ischemic stroke.